2006
DOI: 10.2193/0022-541x(2006)70[1119:dpsipt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Particle Size Ingestion: Promoting Target-Specific Baiting of Feral Cats

Abstract: Predation by feral cats (Felis catus) is believed to threaten the conservation of a range of terrestrial vertebrates in southeastern Australia, and new baiting techniques are sought for broad‐scale control of feral cats. In southeastern Australia there are 34 native mammals that may consume meat baits, and ways to minimize their exposure to bait toxicants are needed. We determined the potential of cats to ingest larger particles relative to most nontarget species as a mechanism to increase baiting selectivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…ERADICAT ® is a sausage bait with a relatively soft/moist texture, consisting mainly of kangaroo meat. Marks et al (2006) provide further description. Feral cats will readily consume this bait (Algar and Burrows 2004).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…ERADICAT ® is a sausage bait with a relatively soft/moist texture, consisting mainly of kangaroo meat. Marks et al (2006) provide further description. Feral cats will readily consume this bait (Algar and Burrows 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ongoing research has revealed two methods that may be used to make feral cat baits more species specific (Marks et al 2006). A synthetic compound named para-aminopropiophenone (PAPP) has been identified as an ideal toxicant for feral cat control given the reported difference in susceptibility between cats and other species as well as other factors such as the apparently humane mode of action (Savarie et al 1983;Marks et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations